Comparison of Fixed-Item and Response-Sensitive Versions of an Online Tutorial. - Grant, Lyle K.; Courtoreille, Marni (Psychological Record)
This study is a comparison of 2 versions of an Internet-based tutorial that teaches the behavior-analysis concept of positive reinforcement. A fixed-item group of students studied a version of the tutorial that included 14 interactive examples and nonexamples of the concept. A response-sensitive group of students studied a different version of the tutorial in which, after an initial round of 10 example and nonexample items, the computer readministered item types the students had answered incorrectly until the students responded correctly to each of 5 example and 5 nonexample item subtypes. A control group studied an online tutorial in biological psychology. Students in all 3 groups took a 10-item pretest and posttest over positive reinforcement. An analysis of the students' change scores indicated that the students learned more using the response-sensitive tutorial than the fixed-item tutorial. Scores of students using both versions of the tutorial were superior to those of the control group. Students using the response-sensitive and fixed-item tutorials required the same amount of study time. Students rated both versions of the positive reinforcement tutorial favorably on several dimensions. Reprinted by permission of the publisher.